Co-learning styles and indicators of digital skills - Barros, Daniela Melaré Vieira (2014)
What is being discussed in education is currently contextualized within the network society, where formal and informal co-learning are indispensable in the development and exercise of social, cultural, cognitive, both technological mastery and fluency as professional on citizenship skills. The main goal of reflection isto identify indicators of co-learning styles that favor the development of digital skills. We present a descriptive analysis supported by bibliographic references, reflections and discussions of space dialog weSPOT Community CoLearn project coordinated by the researcher Alexandra Okada Open University. The results thusbring a contribution to thinking about theories of learning styles and emerging digital skills.